The relationship of heritage trees in urban heat island mitigation effect at Taiping, Perak, Malaysia / Nor Suhaida Yusof, Nur Huzeima Mohd Hussain and Noradila Rusli - Nor Suhaida, Yusof; Nur Huzeima Mohd Hussain, Mohd Hussain; Noradila, Rusli (Universiti Teknologi MARA Cawangan Perak, 2017)
Every tree species provide different cooling effect depending on their tree characteristics. Evergreen species such as heritage trees are significant in reducing the surface temperature. The aim of this paper is to determine the relationship of heritage treesin mitigating urban heat island at Taiping Old Town. The research had been conducted through Landsat 8 OLI and field data collection. Thisresearch integrated the Geographic Information System (GIS) and remote sensing in data processing and analysis. The results show the low significant relationship of tree characteristics and Land Surface Temperature (LST) with (R²=0.17) which indicate that external factors may also influence the changes in temperature.